Design and development of automatic NGV natural gas vehicle refuelling robot / Mohd Noorshahril Yaakob - Mohd Noorshahril, Yaakob (2013)
This project paper is aimed to plan and develop an automatic robot for an application of refueling the natural gas vehicle (NGV) with main focus on its trajectory analysis. A KUKA KR16 L6-2 KS robotic arm is chosen to model the kinematics and motion to perform the task, simulated using KUKA SimPro software, taking advantage of its off-line programming capabilities. Two case studies were investigated in the process of modeling, taking into account on the position of fuel filling valve on the vehicle, whether it is horizontally-placed or vertically-placed, where six and five movement points are pre-defined respectively. Also, the point of interests for each case study, namely the end-effector point and the fuel filling point, are pre-defined based on feasible and actual environment. All the points are used for programming by applying the point-to-point (PTP) motion to be loaded into the KR C2 controller. The transformation matrices are derived at each point and also for total robot motion using the forward kinematics approach beside representing the kinematics of each robot joint using Denavit-Hartenberg approach. The angles of each joint at each movement points are calculated using the inverse kinematics approach to provide the significant boundary conditions for determining the overall rotational motion of the robot. Furthermore, the angles calculated are mapped for the robot trajectories at given time using third-order polynomial trajectory planning to give the extended view of the robot orientation and behavior in order to perform the simple task of vehicle refueling.